Tocilizumab Efficacy in a Patient with Positive Anti-CCP Chronic Lyme Arthritis - Hirsch, Julianna (N Am J Med Sci, 2016)
CONTEXT: Lyme arthritis, a manifestation of tick-borne Lyme disease, can prove to be refractory to classic treatment. CASE REPORT: We present a case of a 48-year-old male, diagnosed with chronic Lyme arthritis, refractory to recurrent and prolonged courses of doxycycline, ceftriaxone, as well as hydroxychloroquine and methotrexate. The patient responded partially to tumor necrosis factor (TNF)-alpha blockade by etanercept and, finally, entered long-term remission after his treatment was switched to tocilizumab. CONCLUSION: Off label treatment by biologic disease modifying antirheumatic drugs can be considered in selected patients with severe antibiotic-resistant Lyme arthritis.C.